Management in product IT companies: new organisational approaches and personnel challenges - I.V. Zhalinska; O.S. Maksiutenko (Економіка, управління та адміністрування)
The global shift from service-oriented to product-based business models in the IT industry has led to profound transformations in corporate strategy, organizational structure, and workforce composition. This article explores the defining features of product IT companies, distinguishing them from traditional service providers through their proprietary product ownership, long-term strategic orientation, and cross-functional team models. It presents a multi-layered classification of product IT companies by product type, business model, and lifecycle stage, focusing on their increasing specialization across industry verticals. Furthermore, the paper analyzes key workforce transformations driven by two interrelated forces: the evolution of product-based business logic and the integration of artificial intelligence (AI) technologies. The growing demand for interdisciplinary, non-engineering roles, such as product managers, UX designers, and data analysts, highlights the necessity of hybrid skills and adaptability in the digital era. Simultaneously, AI is reshaping job profiles, automating routine tasks, and introducing new hybrid roles like AI product strategists and prompt engineers. These trends necessitate a rethinking of talent strategies and call for continuous upskilling, internal leadership development, and agile HR policies. The article draws upon recent academic and industry research to show that structural adaptability, strategic alignment, and a dynamic approach to workforce development are becoming critical to competitiveness in product-oriented IT enterprises. The study also outlines future directions for research on human-AI collaboration and meta-competency cultivation in digital product teams.